Beautiful world : piano, vocal, chords - Brickman, Jim (Alfred, 2009)
The uplifting songs of Beautiful World are now yours to play on the piano. All the songs from the CD are available for piano with chords and vocals. The songs that were inspired by Jim<U+2019>s travels are perfect for weddings, memorials, recitals and sharing with family and friends.